The L Word - eLas por eLas: e o universo lésbico se apresenta na TV - Adriana Agostini de Resende (2010)
This thesis is geared towards portraying the lesbian universe through the analysis of five characters from the TV series The L Word. We aim to provide our readers with reasons as to why this series was such a worldwide success, obtaining fans from all four corners of the earth, including those from countries that didnt air the series. Our study will focus more specifically on the observation of the different ways its narrative is presented and speaks to its audience. To achieve this, we addresses the issue of lesbian identity in addition to discussing thestatus of television in an era in which new technologies enable the audience closer contact. Moreover, this research also briefly addresses the history and some of the possible TV series formats. With basis on The L Word series reviews and critics and by putting into practice the proposed thesis title elas por elas (them by them1), we are able to notice with precision how intensely all crew members became involved in the making of this series not only duri ng its shooting but also behind its scenes. After focusing on theories applied to each individual character, this thesis aims to identify traces of the lesbian universe depicted by the series characters thereby consequently offering its spectators, especiallythose who are lesbian, a wide range of identification options.